Document Digitalization and Scoring System of Students Final Project - Meliana Christianti Johan; Robby Tan; Bernard Renaldy Suteja; Nurul Afiany (Maranatha University Press, 2020)
The Faculty of Information Technology is one of the faculties at Maranatha Christian University Bandung. One of the study programs in the Faculty of Information Technology is Informatics Engineering Department. Nowadays, the management of Final Project and Final Project Seminar is still managed manually. In this research, we did this research to digitalize any documents and scoring grades by using this system for student’s final project. This causes the data management process related to the process of recording and completing the final project relying only on Microsoft Excel. In this research, an analysis and application design carried out to assist the process of recording the journey of students in completing the Final Project Assignment. The result from this research is an application prototype that can be used by course coordinators to manage grades of final project and final project seminar. This application is a web-based, built using PHP with Firebase database.